2006
DOI: 10.1103/physrevb.74.024206
|View full text |Cite
|
Sign up to set email alerts
|

Metal-insulator transition in random Kronig-Penney superlattices with long-range correlated disorder

Abstract: We study the electronic properties of disordered GaAs-AlxGa1−xAs semiconductor superlattices with structural long-range correlations. The system consists of quantum barriers and wells with different thicknesses and heights which fluctuate around their mean values randomly, following a long-range correlated pattern of fractal type characterized by a power spectrum of the type S(k) ∝ 1/k (2α−1) , where the exponent α quantifies the strength of the long-range correlations. For a given system size, we find a criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 28 publications
(20 reference statements)
1
23
0
3
Order By: Relevance
“…Recently, analytical as well as numerical studies revealed that delocalized electronic states can exist in a one-dimensional disordered lattice with short-range [3][4][5][6][7] and long-range [8][9][10][11][12][13][14][15][16][17] correlations. In addition, from the scaling theory [21] it is well known that an infinitesimal disorder can cause localization of all states in one-and two-dimensional systems in the thermodynamic limit.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, analytical as well as numerical studies revealed that delocalized electronic states can exist in a one-dimensional disordered lattice with short-range [3][4][5][6][7] and long-range [8][9][10][11][12][13][14][15][16][17] correlations. In addition, from the scaling theory [21] it is well known that an infinitesimal disorder can cause localization of all states in one-and two-dimensional systems in the thermodynamic limit.…”
Section: Introductionmentioning
confidence: 99%
“…A partir de la secuencia con correlación de largo alcance {v j }, generamos la distribución de tres valores de capacitancias C A , C B y C 0 , según el siguiente mapeo [13]:…”
Section: Caso Con Parámetro De Correlación De Largo Alcance αunclassified
“…El estudio del grado de localización de la función de onda cuántica, en sistemas desordenados con correlación de corto y largo alcance en el desorden, ha sido objeto de gran atención en el último tiempo [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Recientemente se ha introducido correlación de largo alcance en el desorden a través del proceso de "dilución" de los sistemas desordenados [7][8][9][10][11][12].…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Experimental evidence for discrete the number of the extended states has been observed in random-dimer semiconductor superlattices as a short-range correlated disorder 25 . Long-range correlated sequences of the potential barriers in semiconductor superlattices, however, could result in a continuum of extended states giving rise the mobility edges [26][27][28] . In this paper, we study the conductance of massless Dirac fermions through graphene superlattices with a long-range correlated disorder on the potentials of the barriers.…”
Section: Introductionmentioning
confidence: 99%